PENGARUH INDEPENDENSI, OBJEKTIVITAS, PENGALAMAN KERJA, INTEGRITAS DAN KOMPETENSI TERHADAP KUALITAS AUDIT (Studi Empiris pada Pemeriksa BPK RI Perwakilan Provinsi Jawa Tengah) (Students' Journal of Accounting and Banking, 2013)
The objectives of this research to empirically analyse the influence of independency, objectivity, job experience, integritas, competency on quality of audit especially in the external auditor working in BPK RI Province in Central of Java. The population in this research are all auditors which have followed Education and Training of Functional Position of Auditor (Diklat JFP). Sampling was conducted using a purposive sampling method and number of samples of 75 respondents. Primary data collection method used is multiple regression model. The result showed that objectivity and integrity have a position impact on audit quality. And independency, job experience and competency doesn’t have a position impact on audit quality Keywords : independency, objectivity, job experience, integrity, competency, quality of audit.